A Qualitative Study on the Impact of Sexual Assault and Its Approach to Cope with in Female Teenage Victims in Surakarta, Central Java - Nila Widya Keswara; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Studies have shown that sexual assault can lead to the profound impact on the victims. It may last short or long, and can even generate a